Approaching Stan Laurel's Illusion: The Self-Induced Rubber Hand Phenomenon. (August 2013) - Neuf, Hartmut; Hamburger, Kai
The classical rubber hand illusion is induced by an experimenter (eg stimulation with a brush) and usually realized with some sort of visual occlusion. Here, we demonstrate a new phenomenon: The self-induced rubber hand illusion. It is possible to elicit the feeling of a third hand without any help from an experimenter and under conditions of no occlusion. The findings are discussed within the context of neural plasticity.